Interatrial septum dissection and atrial wall hematoma following transseptal puncture: A systematic review of the literature. Issue 2 (23rd October 2019) - Meier, David; Antiochos, Panagiotis; Herrera‐Siklody, Claudia; Eeckhout, Eric; Delabays, Alain; Tzimas, Georgios; Fournier, Stephane; Pascale, Patrizio; Muller, Olivier; Monney, Pierre
Abstract: Background: Interatrial septum (IAS) dissection due to transseptal puncture (TSP) is a rare, underreported complication of the procedure. Data on the mechanism, diagnosis, and management of this complication are lacking. Methods: We conducted a systematic review of all reported cases of IAS dissection with or without associated LA hematoma due to TSP, by thoroughly searching MEDLINE and EMBASE through May 2019. Results: After screening of n = 882 studies, eight studies with a total of 19 patients addressed the complication of IAS dissection and/or LA hematoma secondary to TSP. Median age was 63 years with a 1:1 male to female ratio. Ablation of atrial fibrillation was the most frequently reported procedure (84%). Diagnosis was established using fluoroscopy with contrast injection (58%), TEE (32%) or intracardiac echocardiography (5%). The mechanism identified involved puncture of the septum secundum portion of the IAS, leading to transient needle passage into the extracardiac space. In the majority of patients, the hematoma remained localized in the IAS and management was conservative with progressive resolution of the hematoma during follow‐up (95%). Two patients (11%) required further intervention by either pericardiocentesis or surgical drainage due to hemodynamic instability. Conclusions: IAS dissection with or without hematoma after TSP remains an underdiagnosed entity. The main mechanism involves lesion to the septum secundum portion of the IAS, resulting in needle passage into the extracardiac space and local bleeding. Although conservative management may be sufficient in the majority of cases, interventional cardiologists should be familiar with this complication and its diagnosis.